Association of genomic variants at the human leukocyte antigen locus with cervical cancer risk,HPVstatus and gene expression levels - Ramachandran, Dhanya; Schuermann, Peter; Mao, Qianqian; Wang, Yingying; Bretschneider, Lisa-Marie; Speith, Lisa-Marie; Huelse, Fabienne; Enssen, Julia; Bousset, Kristine; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; et al. (International Journal of Cancer, 2020)
The human leukocyte antigen (HLA) locus on chromosome 6 has been reported to be associated with cervical cancer. We investigated two independent single-nucleotide polymorphisms in a large case-control series of cervical dysplasia and carcinoma that has been newly established by the German Cervigen Consortium, comprising a total of 2481 cases and 1556 healthy females. We find significant associations for both variants, rs9272117 atHLA-DQA1and rs2844511 atMICAandHCP5, with cervical disease. Both variants showed evidence of association with invasive cervical cancer (rs9272117: OR 0.89, 95% CI 0.79-0.99,P= .036; rs2844511: OR 1.17, 95% CI 1.04-1.31,P= .008) and with high-grade dysplasia (rs9272117: OR 0.78, 95% CI 0.70-0.87,P= 7.1 x 10(-6); rs2844511: OR 1.13, 95% CI 1.01-1.26,P= .035), as well as in a combined analysis of both groups (rs9272117: OR 0.83, 95% CI 0.75-0.91,P= 6.9 x 10(-5); rs2844511: OR 1.14, 95% CI 1.04-1.26,P= .005). Variant rs2844511, but not rs9272117, also showed modest evidence of association with low-grade dysplasia (OR 1.26, 95% CI 1.04-1.54,P= .019). In case-only analyses, rs2844511 tended to predict HPV status (P= .044) and rs9272117 tended to associate with HPV16 (P= .022). RNA studies in cervical samples showed a significant correlation in the transcript levels ofMICA,HCP5andHLA-DQA1, suggesting extensive co-regulation. All three genes were upregulated in HPV16-positive samples. In stratified analyses, rs9272117 was associated withHLA-DQA1levels, specifically in HPV-positive samples, while rs2844511 was associated withMICAandHCP5levels. The risk allele of rs2844511 was required for correlations betweenMICAorHCP5withHLA-DQA1. Altogether, our results support 6p21.32-33 as the first consistent cervical cancer susceptibility locus and provide evidence for a link between genetic risk variants, HPV16 status and transcript levels ofHLA-DQA1,HCP5andMICA, which may contribute to tumor immune evasion.
CRIS-Team WoS Importer:2020-07-24